Improvement in extracellular protease production by the marine antarctic yeast Rhodotorula mucilaginosa L7 - Chaud, Luciana C.S. (2016)
Microorganisms from extreme and restrictive eco systems, such as the Antarctic continent, are of great interest due to their ability to synthesize products of commercial value. Among these, enzymes from psychrotolerant and psychrophilic microorganisms offer potential economical benefits due to their high activity at low and moderate temperatures. The cold adapted yeast Rhodotorula mucilaginosa L7 was selected out of 97 yeasts isolated from Antarctica as having the highest extracellular proteolytic activity in preliminary tests. The present study was aimed at evaluating the effects of nutrient composition (peptone, rice bran extract, ammonium sulfate, sodium chloride) and physicochemical parameters (temperature and pH) on its proteolytic activity. A 26−2 fractional factorial design experiment followed by a central composite design (CCD 23) was performed to optimize the culture conditions and improve the extracellular proteolytic activity. The results indicated that the presence of peptone in the medium was the most influential factor in protease production. Enzymatic activity was enhanced by the interaction between low glucose and peptone concentrations. The optimization of culture conditions with the aid of mathematical modeling enabled a c. 45% increase in proteolytic activity and at the same time reduced the amount of glucose and peptone required for the culture. Thus culture conditions established in this work may be employed in the biotechnological production of this protease.